Identification of Grass Weeds in Florida Citrus - Stephen H. Futch; David W. Hall (EDIS)
Grass weeds commonly found in citrus can be identified by looking for specific characteristics of the plant. The 12 grass plants discussed in this article are weeds commonly found in citrus groves and other disturbed and cultivated sites in the state of Florida. The characteristics discussed in this article should help you with identification. This document is HS955, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2004.